(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Results of biomorphological, geographic and ecological-coenotic analyses of 113 plant species from the Red Data Book of Ukraine (2009) which are cultivated in collection plot “Rare and endangered plants of the natural flora of Ukraine” in the O.V. Fomin Botanical Garden of the National Taras Schevchenko University of Kyiv are given in the article. Perspective groups of rare plants according to their biomorphological, geographical, ecological and coenotic opportunities were selected for future successful introduction investigations. We believe that further introduction researches should focus on zonal rare species which are represented in flora of Kyiv and Kyiv region. Introduction investigations of other species should continue only in special exhibits that their conditions meet ecological-coenotic needs of these species. Also information about the cultivation of plants from "Red Book of Ukraine" in introduction centers of Ukraine are given in the article.